2021
DOI: 10.3390/molecules26092781
|View full text |Cite
|
Sign up to set email alerts
|

Biological Applications of Electron Paramagnetic Resonance Viscometry Using a 13C-Labeled Trityl Spin Probe

Abstract: Alterations in viscosity of biological fluids and tissues play an important role in health and diseases. It has been demonstrated that the electron paramagnetic resonance (EPR) spectrum of a 13C-labeled trityl spin probe (13C-dFT) is highly sensitive to the local viscosity of its microenvironment. In the present study, we demonstrate that X-band (9.5 GHz) EPR viscometry using 13C-dFT provides a simple tool to accurately measure the microviscosity of human blood in microliter volumes obtained from healthy volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
(111 reference statements)
2
5
0
Order By: Relevance
“…The linewidth of 1.1 ± 0.1 G corresponds to a tissue viscosity of 1.14 ± 0.1 cP, in good agreement with literature data. 20,30 This result confirms that 13 C 1 -OX071 can be used to measure tissue viscosity in vivo upon systemic delivery. The study of tissue microviscosity as a biomarker of cancer is beyond the scope of this paper and will be reported elsewhere.…”
Section: L-band In Vivo Epr Viscometry In Tumorsupporting
confidence: 72%
“…The linewidth of 1.1 ± 0.1 G corresponds to a tissue viscosity of 1.14 ± 0.1 cP, in good agreement with literature data. 20,30 This result confirms that 13 C 1 -OX071 can be used to measure tissue viscosity in vivo upon systemic delivery. The study of tissue microviscosity as a biomarker of cancer is beyond the scope of this paper and will be reported elsewhere.…”
Section: L-band In Vivo Epr Viscometry In Tumorsupporting
confidence: 72%
“…Below a microviscosity of 6 cP, the spectrum of 13 C 1 -dFT is a doublet, and the effect of viscosity is a line broadening (820 mG/cP at X-band, 9.5 GHz) affecting both lines equally because of the minimal g anisotropy of the probe ( g x = 2.0033, g y = 2.0032, g z = 2.00275). We demonstrated that this water-soluble radical could be used in vitro, ex vivo, and in vivo to measure microviscosity by EPR . Perchlorinated triarylmethyl radicals constitute another class of trityls used in biomedical EPR to measure oxygen in vivo, , detect superoxide , or hydroxyl radical, and as hyperpolarizing agents for a dynamic nuclear polarization (DNP) , or in material sciences. , A perchlorotriarylmethyl tricarboxylic acid radical ( PTMTC ) 50% enriched 13 C 1 was reported recently by Elewa et al The authors showed that the line widths of the doublet arising from the hyperfine interaction with the 13 C 1 were also strongly sensitive to viscosity.…”
Section: Introductionmentioning
confidence: 86%
“…We demonstrated that this water-soluble radical could be used in vitro, ex vivo, and in vivo to measure microviscosity by EPR. 12 biomedical EPR to measure oxygen in vivo, 13,14 detect superoxide 15,16 or hydroxyl radical, 17 and as hyperpolarizing agents for a dynamic nuclear polarization (DNP) 18,19 or in material sciences. 20,21 A perchlorotriarylmethyl tricarboxylic acid radical (PTMTC) 50% enriched 13 C 1 was reported recently by Elewa et al 22 The authors showed that the line widths of the doublet arising from the hyperfine interaction with the 13 C 1 were also strongly sensitive to viscosity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Serum samples isolated from blood collected at euthanasia from infected ( n = 6) versus noninfected groups ( n = 6) were frozen and stored at −80°C. Our approach for measuring the oxidizing potential of rat serum samples using EPR spectrometry and the spin probe 1‐hydroxy‐3‐carboxymethyl‐2,2,5,5‐tetramethyl‐pyrrolidine (CMH) (Enzo Life Science, Farmingdale, NY) was comparable to that described by Majumdar et al and Velayutham et al 25,26 Serum (0.1 mL) was incubated with CMH at 37°C for 30 min (0.2 mM). Serum oxidants oxidize CMH (EPR inactive) to 3‐carboxymethyl‐2,2,5,5‐tetramethylpyrrolidinyloxy radical (CM; EPR active).…”
Section: Methodsmentioning
confidence: 99%